Optimized differential thermal analysis sheds light on the effect of temperature on peach floral bud cold hardiness and transition from endo- to ecodormancy - Sterle, David G (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 Elsevier B.V. All rights reserved.